2008
DOI: 10.1177/00333549081230s305
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Patient Acceptance of Opt-in, Universal, Rapid HIV Screening

Abstract: SYNOPSISObjectives. We assessed emergency department (ED) patient acceptance of opt-in, rapid human immunodeficiency virus (HIV) screening and identified demographic characteristics and HIV testing-history factors associated with acceptance of screening.Methods. A random sample of 18-to 55-year-old ED patients was offered rapid HIV screening. Patient acceptance or decline of screening and the reasons for acceptance or decline were analyzed with multivariable regression models. Odds ratios (ORs) with 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
87
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 19 publications
5
87
1
Order By: Relevance
“…Nonetheless, the acceptance rate in our program is much higher than that noted in most testing programs that have offered routine HIV screening. [13][14][15][16][17][18][19]28,30 Although many of these routine HIV screening programs demonstrated that over half of the patients tested will accept testing, most used screening models that required separate consent for HIV testing or for study participation and did not use the opt-out approach currently recommended by the CDC. Our findings illustrate that streamlining the consent and counseling procedures and the opt-out approach for HIV testing in health care settings may promote high test acceptance in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the acceptance rate in our program is much higher than that noted in most testing programs that have offered routine HIV screening. [13][14][15][16][17][18][19]28,30 Although many of these routine HIV screening programs demonstrated that over half of the patients tested will accept testing, most used screening models that required separate consent for HIV testing or for study participation and did not use the opt-out approach currently recommended by the CDC. Our findings illustrate that streamlining the consent and counseling procedures and the opt-out approach for HIV testing in health care settings may promote high test acceptance in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…18 Most routine HIV testing programs did not include testing the pediatric population. [13][14][15]17,32 However, of the studies that tested pediatric patients, few have tested individuals as young as age 13 years, who had the lowest acceptance rate in our program. Because our pediatric patients were often accompanied by a parent, it is possible that parental influence affected test acceptance among pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Sample size to test the primary hypothesis of testing uptake difference was estimated using a binomial tests of proportions, with power = 0.80 and alpha = 0.05 and was estimated to be 79 per study arm. To allow for potential attrition during the study (based on our prior research experience, estimated to be between 10 and 15%), we enrolled as many additional participants as possible during the recruitment period.…”
Section: Discussionmentioning
confidence: 99%
“…Our acceptance for screening is similar to that reported nationally (45%), 1 but not as high as acceptance for STI or HIV testing reported in previous ED studies. 24 In the ED, as in many other health care sites, screenings for STIs are not part of recommended care. 26 However, in our sample, as is the case nationally, the majority of those who are recommended for annual screening for chlamydia and gonorrhea did not accept testing.…”
Section: Discussionmentioning
confidence: 99%